Síntese e Estudo termodinâmico em adutos de trihaletos de Antimônio e Bismuto com 2,2 - Bipiridina e 1,10- Fenantrolina - Martins, Evandro Paulo Soares (2010)
In this work were synthesized, characterized and studied experimentally and theoretically, the compounds of general formula [MX3 (L)], where M = Sb or Bi, X = Cl, Br, L = 2,2'-bipyridine (Bpy), 1,10-phenanthroline (Phen). The synthesized compounds were characterized by elemental analysis (C, H, N, Cl and Br), thermal analysis (TG / DTA) and absorption spectroscopy in the infrared region. The results of elemental analysis suggest a stoichiometry of 1:1 salt / ligand in agreement with the stoichiometry suggested by thermogravimetric analysis. The infrared data of the ligands when compared with those of the adducts indicate a strengthening of the CC bonds, CN the aromatic ring with the coordination.The Thermochemical parameters were obtained experimentally by solution calorimetry. The enthalpy of reaction, acid-Lewis base, determined by calorimetry indicate the strongest basic character of Phen compared to metals. Enthalpies of metal-nitrogen bond follows the order of bonding strength: [BiBr3(Phen)] > [SbCl3(Phen)] > [BiBr3(Bpy)] > [SbCl3(Bpy)]. The theoretical studies were aimed to the structural properties and thermochemistry in the gas phase, through the semi-empirical PM3 method. The results of the calculations predict a geometry type distorted square pyramidal for all the adducts studied, indicating the strong influence of the lone pair of electrons of metals over distance of bond metal-nitrogen. Dipole moments are calculated in the range 10-14D, suggesting a large polar character of the compounds studied.